2015
DOI: 10.1039/c4mt00250d
|View full text |Cite
|
Sign up to set email alerts
|

Copper trafficking in the CsoR regulon of Streptomyces lividans

Abstract: In the actinobacterium Streptomyces lividans copper homeostasis is controlled through the action of the metalloregulator CsoR. Under copper stress, cuprous ions bind to apo-CsoR resulting in the transcriptional derepression of genes encoding for copper efflux systems involving CopZ-like copper chaperones and CopA-like P-type ATPases. Whether CsoR obtains copper via a protein-protein mediated trafficking mechanism is unknown. In this study we have characterised the copper trafficking properties of two S. livida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 62 publications
0
38
0
Order By: Relevance
“…To maintain the copper homeostasis, cytosolic copper is precisely regulated by resistance proteins. The twocomponent system was previously confirmed as the key regulatory system for the extra-cytoplasmic sensing of elevated copper ion and can regulate the expression of related genes to elicit adaptive responses to changes in the concentration of copper (Chaplin et al 2015;Singh et al 2014). Here, we found a total of 8 genes in the genome of S. erythraea NRRL23338 that are potentially involved in copper metabolism.…”
Section: Determination Of the Relative Transcript Levels Of Copper-rementioning
confidence: 65%
“…To maintain the copper homeostasis, cytosolic copper is precisely regulated by resistance proteins. The twocomponent system was previously confirmed as the key regulatory system for the extra-cytoplasmic sensing of elevated copper ion and can regulate the expression of related genes to elicit adaptive responses to changes in the concentration of copper (Chaplin et al 2015;Singh et al 2014). Here, we found a total of 8 genes in the genome of S. erythraea NRRL23338 that are potentially involved in copper metabolism.…”
Section: Determination Of the Relative Transcript Levels Of Copper-rementioning
confidence: 65%
“…1B). This His is likely responsible for the higher Cu ϩ affinity observed in P. aeruginosa CopZ2 (15), as it has been shown that its removal decreases S. lividans CopZs affinity for Cu ϩ (25). Moreover, the His is probably determinant of their different behavior in the presence of Cu ϩ where CopZ2 (but not CopZ1) forms Cu ϩ -mediated multimeric structures even with equimolar Cu ϩ as observed in native PAGE gels (Fig.…”
Section: Copz1 and Copz2 Have Distinct Roles In P Aeruginosamentioning
confidence: 82%
“…Both are under control of CueR, binding Cu ϩ with 1:1 stoichiometry and high affinity, CopZ1 4 ϫ 10 Ϫ15 M and CopZ2 8 ϫ 10 Ϫ17 M (15). This multiplicity of copper chaperones has been also observed in Streptomyces lividans that has four CopZ-like Cu ϩ chaperones (25). Even though their Cu ϩ affinities have been determined (CopZ-1317 10 Ϫ17 M and CopZ-3079 10 Ϫ18 M), their possible function is obscure as they both appear to interact similarly with CsoR.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…In the absence of copper, two CsoR tetramers clutch the operator region to prevent transcription On: Fri, 11 May 2018 06:47:07 (Chaplin et al, 2015). For induction of transcription by copper, four Cu + per homotetramer bind cooperatively to a C and an H residue on one subunit and a C residue of the adjacent subunit (Jacobs et al, 2015).…”
Section: Discussionmentioning
confidence: 99%